Do Genital Cosmetic Procedures Improve Women's Self-Esteem? A Systematic Review and Meta-Analysis. (5th February 2020) - Sharp, Gemma; Maynard, Pascale; Hudaib, Abdul-Rahman; Hamori, Christine A; Oates, Jayson; Kulkarni, Jayashri; Sarwer, David B
Abstract: Background: The popularity of genital cosmetic procedures in women is increasing. These procedures are often assumed and promoted as having a positive effect on women's psychological well-being, particularly their self-esteem. Empirical support for these claims is lacking. Objectives: The aim of this study was to conduct a systematic review and meta-analysis of the impact of genital cosmetic procedures on self-esteem in women. Methods: The authors performed a systematic literature review of MEDLINE, PreMEDLINE, Ebase, EMBASE, OVID, CINAHL, Cochrane, PsycINFO, and PubMed to identify articles that measured self-esteem in women after a genital cosmetic procedure. A meta-analysis was conducted to assess the pooled effect of these procedures on self-esteem. Results: The authors identified 5 eligible studies for the meta-analysis, comprising 2 prospective and 3 retrospective studies. Labia minora reduction was the most commonly studied procedure. All 5 studies used different measures of self-esteem, with only 1 study employing a validated psychometric measure at both preoperative and postoperative time points. The meta-analysis results showed a pooled logit rate estimate of 1.230, indicating a positive effect of surgery on self-esteem. However, there was substantial heterogeneity across studies. Conclusions: Female genital cosmetic procedures, particularly labiaplasty, appear to have a positive effect on women's self-esteem. However, inconsistencies in study measures and methods limit our conclusions. Future research should involve the development of standardized outcome measures to more accurately assess the impact of these procedures on self-esteem, and on psychological well-being more generally. Level of Evidence: 3: